Standards-based external exams and students' science-related career expectations: an international perspective. Issue 7 (16th November 2016) - Han, Seong Won
ABSTRACT: Students' science-related career expectations are important for predicting their future science, technology, engineering, and mathematics (STEM)-related educational and occupational attainments. This study examines the degree to which standards-based external examinations are associated with a student's propensity for pursuing science-related professional occupations. The science-related fields included in the analysis are mathematics, physical and life science, and engineering/computing. Three-level hierarchical generalized linear models are employed to analyse international survey and student achievement data from the Programme for International Student Assessment (PISA). The analyses show that students in national education systems that require standards-based external examinations have lower expectations for science-related professional careers than students in the systems that do not use such examinations. This negative association remained constant by gender as well as across levels of science performance. From an educational policy point of view, the results suggest the negative consequence of standards-based external exams in fostering students' interests in pursuing science-related careers.